Unmet challenges in treating hypertension in patients with borderline personality disorder: A systematic review. Issue 37 (September 2019) - Roininen, Saara M.; Cheetham, Marcus; Mueller, Beatrice U.; Battegay, Edouard
Abstract: Background: Caregivers encounter serious and substantial challenges in managing hypertension in patients with subclinical or clinical borderline personality disorder (BPD). These challenges include therapeutic conflicts resulting from harmful drug–drug, and drug–disease interactions. Current guidelines provide no recommendations for concurrent psychotropic and antihypertensive treatment of hypertensive BPD patients who are at even greater cardiovascular risk. Methods: We conducted a systematic literature review to assess the extent of available evidence on prevalence rates, cardiovascular risk factors, therapeutic conflicts, and evidence-based treatment recommendations for patients with co-occurring hypertension and BPD. Search terms were combined for hypertension and BPD in PubMed, MEDLINE, EMBASE, Cochrane, and PsycINFO databases. Results: We included 11 articles for full-text evaluation and found a very high prevalence of hypertension and substantial cardiovascular risk in studies on co-occurring BPD and hypertension. However, we identified neither studies on harmful drug–drug and drug–disease interactions nor studies with treatment recommendations for co-occurring hypertension and BPD. Conclusions: Increased prevalence of hypertension in BPD patients, and therapeutic conflicts of psychotropic agents strongly suggest careful evaluation of treatment strategies in this patient group. However, no studies or guidelines recommend specific therapies or strategies to resolve therapeutic conflicts in patients with hypertension and BPD. This evidence gap needs attention in this population at high risk for cardiovascular disease. Abstract : Supplemental Digital Content is available in the text